Characterization and Suitability Assessment of Some Pomegranate-growing and Associated Soils of Solapur District, Maharashtra - K. Karthikeyan and Pramod Tiwary, Laxman B. Jadhao, Jagdish Prasad* (Journal of the Indian Society of Soil Science, 2019)
Four pomegranate-growing pedons (P1, P3, P5, P7) and four associated crop land (P2, P4, P6, P8) were characterized for physical and chemical properties, nutritional status of soils and leaves to compute soil-site suitability for pomegranate in Velapur, Adatmala, Bhalwani and Supli villages of Solapur district. Pedons were shallow (